2021
DOI: 10.7150/ijms.48050
|View full text |Cite
|
Sign up to set email alerts
|

Low Radiation X-rays: Benefiting People Globally by Reducing Cancer Risks

Abstract: Modern medical imaging facilitates the diagnosis and treatment of human diseases. However, few people are aware of the cons of radiation exposure from medical imaging. Emerging evidence reveals that cumulative doses of radiation exposure will increase the morbidity and mortality of pertaining cancer. As a special young population, patients with adolescent idiopathic scoliosis (AIS) suffer more radiation harms from repeated diagnostic imaging, most of which can be avoided in clinical practice. Accumulating evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…[ 25 ], who concluded that the cumulative dose of 25 mGy is far below the dose threshold for radiogenic cancer, a recent review on low radiation [ 26 ] has shown that neither the medical community nor the public at large is aware enough of the cumulative exposure risks; the current AIS gold diagnostic standard slightly but irrevocably increases the risk of cancer. Since low/zero radiation imaging techniques are nowadays available (the microdose EOS, raster stereography, 3D ultrasound scolioscan), a question arises whether this is the path to follow to reduce potential harm [ 26 ]?…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ], who concluded that the cumulative dose of 25 mGy is far below the dose threshold for radiogenic cancer, a recent review on low radiation [ 26 ] has shown that neither the medical community nor the public at large is aware enough of the cumulative exposure risks; the current AIS gold diagnostic standard slightly but irrevocably increases the risk of cancer. Since low/zero radiation imaging techniques are nowadays available (the microdose EOS, raster stereography, 3D ultrasound scolioscan), a question arises whether this is the path to follow to reduce potential harm [ 26 ]?…”
Section: Discussionmentioning
confidence: 99%
“…X-rays and CT are commonly used for the diagnosis of chest diseases. CT can present three-dimensional images as a way to analyze the relationship between tumor tissues and their surroundings; X-ray imaging can diagnose the origin of the tumor, such as chest wall tumor bone or from soft tissue [ 10 ] in X-ray and benign soft tissue tumors image as round or oval shadows of masses with uniform distribution and clearer and more definite margins in local areas. In contrast, malignant tumors exhibit lamellar shadows with curved, lobulated edges [ 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the focal tissue of the lesion absorbs the same coefficient of X-rays as the adjacent normal tissue in the early stage of development, it is very easy to misdiagnose and miss the diagnosis by using X-ray techniques. However, X-ray and CT diagnosis after tissue 3 Disease Markers lesions have reached a certain degree, or lesions have formed may delay the optimal treatment opportunity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation hazards are an unavoidable risk in X-ray imaging, and although the cumulative amount is not large, it cannot be excluded from cancer risk [17]. Under specific conditions, such as the first trimester period of pregnancy, X-ray imaging is considered an absolute contraindication as it may directly harm the fetus [18].…”
Section: Plain Radiographymentioning
confidence: 99%